Profitable Consideration of Education for Sustainability Development (ESD) above a Time: Bibliometric Analysis - Putri Amelia Solihah; Ida Kaniawati; Achmad Samsudin; Riandi Riandi (Universitas Lambung Mangkurat, 2024)
The objective of this study is to provide a concise overview of research on education for sustainable development, focusing on scientific production, prominent researchers, nations involved, and research topics. An analysis of the scholarly output on the topic of education for sustainability development was conducted using bibliometric methods, focusing on publications published from 2013 to 2023. A total of 19,801 articles were retrieved from Scopus databases. Collecting data was finished, and the data was stored in two specific file formats, namely *.ris and *.csv. The *.ris format serves as the data mapping format in the R Studio and VOSviewer applications, while the *.csv format is utilized for data analysis in Ms. Excel. These papers were published in various publications related to sustainability, social sciences, engineering, and scientific education. The primary findings indicate that the quantity of articles about education for sustainability development is reasonably consistent from 2013 to 2023. Co-authorship relationships primarily involve researchers from the same nation. Furthermore, a change in the research priorities was noted. Prior research has been extensively conducted in various fields, including sustainability, social sciences, engineering, science education, and others. A recent study has highlighted the significance of curriculum and curriculum development. The research implication is bibliometric analysis, which can help identify research trends related to education for sustainability (ESD). This may include the latest research, topic focus, and recent developments in the field.Profitable Consideration of Education for Sustainability Development (ESD) above a Time: Bibliometric Analysis